Leiomodin-3 dysfunction results in thin filament disorganization and nemaline myopathy - Michaela Yuen; Sarah A. Sandaradura; James J. Dowling; Alla S. Kostyukova; Natalia Moroz; Kate G. Quinlan; Vilma-Lotta Lehtokari; Gianina Ravenscroft; Emily J. Todd; Ozge Ceyhan-Birsoy; David S. Gokhin; Jérome Maluenda; et al. (The Journal of Clinical Investigation, 2014)
Nemaline myopathy (NM) is a genetic muscle disorder characterized by muscle dysfunction and electron-dense protein accumulations (nemaline bodies) in myofibers. Pathogenic mutations have been described in 9 genes to date, but the genetic basis remains unknown in many cases. Here, using an approach that combined whole-exome sequencing (WES) and Sanger sequencing, we identified homozygous or compound heterozygous variants in LMOD3 in 21 patients from 14 families with severe, usually lethal, NM. LMOD3 encodes leiomodin-3 (LMOD3), a 65-kDa protein expressed in skeletal and cardiac muscle. LMOD3 was expressed from early stages of muscle differentiation; localized to actin thin filaments, with enrichment near the pointed ends; and had strong actin filament-nucleating activity. Loss of LMOD3 in patient muscle resulted in shortening and disorganization of thin filaments. Knockdown of lmod3 in zebrafish replicated NM-associated functional and pathological phenotypes. Together, these findings indicate that mutations in the gene encoding LMOD3 underlie congenital myopathy and demonstrate that LMOD3 is essential for the organization of sarcomeric thin filaments in skeletal muscle.